KERAGAMAN GULMA PADA TANAMAN KELAPA SAWIT (Elaies guineensis Jacq.) BELUM MENGHASILKAN DAN SUDAH MENGHASILKAN DI KEBUN RAMBUTAN PT. PERKEBUNAN NUSANTARA III - Ahmad Saleh; M Yusuf Dibisono; Sabar Ukur Gea (Institut Teknologi Sawit Indonesia, 2020)
Weeds are undesirable plants because they can compete with the oil palm. Weed growth can reduce the production of bunches by 20%. Weeds are not only due to competition against nutrients but also produce allelopathic substances that are toxic to oil palm. Inventory and find out the dominance of weed species is needed in the management of effective weed control. The study aims to determine the diversity of weeds in different areas of planting year. This study used a sampling method carried out on two mature areas (18 years and 8 years) and an immature area (1 year), with the direct observation method. Every planting area is made of 2 large plots with a size of 20 m x 60 m at interrow of palm, then inside there are made 6 small plots with a size of 2 x 2 m. Data were analyzed with SDR (Summed Dominance Ratio) value to determine the dominant weed species. The diversity of weeds from each area is varied, there are 29 species of weeds and 20 families, nevertheless, there are 5 species of weeds found in all areas of study; O. nodusa, Poaceae; C. kyllingia, Cyperaceae; A. comressus, Poaceae; P. Niruri, Phyllanthaceae; A. spinous, Amaranthaceae. The dominant weeds in the immature area are E. indica, Poaceae while in the mature areas are O. nodosa, Poaceae.